The value of progen, arsanilic acid, and Terramycin antibiotic in the ration of fattening pigs in dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
The use of arsanilic acid in swine rations has been receiving experimental attention for several years. It follows the use of arsenicals that have been used in medical practice hundreds of years. Fowler's solution containing 1 percent arsenic trioxide, a cheap but toxic inorganic arsenic, was first used as a tonic to improve the appearance and well-being of animals. The toxic properties of trioxide, however, greatly limited its use except as a general tonic in veterinary practice.
Keywords: Swine; Progen; Arsanilic acid; Terramycin